The acute effect of beta‐guanidinopropionic acid versus creatine or placebo in healthy men (ABC‐Trial): A randomized controlled first‐in‐human trial - Karamat, Fares A. (Br J Clin Pharmacol, 2017)
AIMS: Increasing evidence indicates that the ATP‐generating enzyme creatine kinase (CK) is involved in hypertension. CK rapidly regenerates ATP from creatine phosphate and ADP. Recently, it has been shown that beta‐guanidinopropionic acid (GPA), a kidney‐synthesized creatine analogue and competitive CK inhibitor, reduced blood pressure in spontaneously hypertensive rats. To further develop the substance as a potential blood pressure‐lowering agent, we assessed the tolerability of a sub‐therapeutic GPA dose in healthy men. METHODS: In this active and placebo‐controlled, triple‐blind, single‐centre trial, we recruited 24 healthy men (18–50 years old, BMI 18.5–29.9 kg m(−2)) in the Netherlands. Participants were randomized (1:1:1) to one week daily oral administration of GPA 100 mg, creatine 5 g, or matching placebo. The primary outcome was the tolerability of GPA, in an intent‐to‐treat analysis. RESULTS: Twenty‐four randomized participants received the allocated intervention and 23 completed the study. One participant in the placebo arm dropped out for personal reasons. GPA was well tolerated, without serious or severe adverse events. No abnormalities were reported with GPA use in clinical safety parameters, including physical examination, laboratory studies, or 12‐Lead ECG. At day 8, mean plasma GPA was 213.88 (SE 0.07) in the GPA arm vs. 32.75 (0.00) nmol l(−1) in the placebo arm, a mean difference of 181.13 (95% CI 26.53–335.72). CONCLUSION: In this first‐in‐human trial, low‐dose GPA was safe and well‐tolerated when used during 1 week in healthy men. Subsequent studies should focus on human pharmacokinetic and pharmacodynamic assessments with different doses.